ANALISIS FAKTOR YANG MEMPENGARUHI MOTIVASI BELAJAR MAHASISWA YANG KULIAH SAMBIL BEKERJA - Nalim Nalim (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
This research tried to uncover the factors that influence the motivation to learn a college student while working, knowing the differences in achievement between students who work full time, part time and students who do not work, knowing the differences in achievement between male students and female, knowing the relationship between the suitability of the type of work with academic achievement, and determine the relationship between the duration of employment with academic achievement. Analysis of the data used in this research is descriptive analysis, factor analysis, t test, one way ANOVA and chi square test. Descriptive analysis was conducted to determine the respondent data manually while factor analysis, t test, one way ANOVA and chi square test was used to analyze the relationship between variables. The results showed that of the 13 factors (variables) that is proposed in this study, all chosen to be a significant factor affecting student learning motivation that works. Of the 13 factors are four main factors that are formed are: (1) the factors of faculty and instructional media, (2) family factors and learning methods, (3) factors and weighting battery campus facilities, and (4) the personal factor and friends. Other findings in this study there was no significant difference between the achievement of students who work full time, part time and that has not worked; There are significant differences in academic achievement between students of both men and women, there is no relationship between the level of conformity of the work with academic achievement, and there is no significant relationship between the duration of working with academic achievement. Keywords: college while working, factor analysis, motivation to learn